An examination of whether the protection of Investment Act represents a successful alternative to bilateral investment treaties - Boyce, Gizelle Marie (Department of Commercial Law, 2017)
The aim of this thesis is to examine whether South Africa's recently promulgated Protection of Investment Act represents a viable alternative to the bilateral investment treaty regime. In undertaking this examination, the bilateral investment treaty regime which preceded the Protection of Investment Act was first reviewed and some of the typical clauses found in these treaties were examined. Pursuant to this examination, the Foresti arbitration, through which a group of Italian and Luxembourgish investors challenged South Africa's affirmative action measures in the mining industry on the basis of the bilateral investment treaties that South Africa had entered into, was then introduced. The author examined the claim made in Foresti, South Africa's response and the final award. The next Chapter then turned to the effects of the Foresti arbitration, which set in motion South Africa's review of the BITs it had entered into, and then the eventual termination of these BITs and replacement with the Protection of Investment Act. In answering the central question of this thesis, a clause by clause analysis of the Protection of Investment Act was conducted in order to determine whether that Act is able to satisfy the deficiencies highlighted in the BIT review pursuant to Foresti. In conducting this analysis, the author highlighted some notable omissions in the Protection of Investment Act. Through this review and comparison, it was concluded that the Protection of Investment Act fails as a viable alternative to the bilateral investment treaty regime for a number of reasons, and in particular for crystallising the flawed BIT regime through a legislative savings provision. A better alternative for South Africa would have been renegotiating historical BITs based on a Model BIT incorporating the necessary amendments to rectify the perceived BIT limitations as highlighted in South Africa's BIT review.